Patient-centred outcomes in the phase 3 study ARIEL3 of rucaparib maintenance treatment in patients with platinum-sensitive, recurrent ovarian carcinoma: post hoc exploratory analyses by BRCA mutation status and patient age. (1st November 2019) - Colombo, N; Oza, AM; Lorusso, D; Aghajanian, C; Oaknin, A; Dean, A; Weberpals, JI; Clamp, AR; Scambia, G; Leary, A; Holloway, RW; Amenedo Gancedo, M; et al.
Abstract : Introduction/Background: Maintenance therapy for recurrent ovarian cancer is intended to extend progression-free survival (PFS) without compromising patient quality of life; therefore, the clinical benefits of prolonged PFS should be evaluated in the context of toxicities that may compromise patients' wellbeing. In ARIEL3 (CO-338-014; NCT01968213 ), rucaparib significantly improved PFS vs placebo in all predefined patient cohorts regardless of biomarker status (Coleman et al. Lancet . 2017;390:1949-61) or age (Ledermann et al. Presented at SGO 2019; abst 4). This post hoc exploratory analysis examined quality-adjusted PFS (QA-PFS) and quality-adjusted time without symptoms or toxicity (Q-TWiST) in patients from ARIEL3, including the subgroup of patients with a BRCA mutation and subgroups based on patient age. Methodology: Patients were randomised 2:1 to oral rucaparib (600 mg BID) or placebo. QA-PFS and Q-TWiST were analysed in patients with a BRCA mutation (germline, somatic, or origin unknown), the ITT population (ie, all randomised patients), and subgroups of the ITT population defined by patient age at baseline (<65, 65–74, or ≥75 years). Q-TWiST was performed using 2 sets of treatment-emergent adverse events (TEAEs): all grade ≥3 TEAEs and grade ≥2 TEAEs of nausea, vomiting, fatigue, and asthenia only. Results: The visit cutoff date for these analyses was 15 April 2017. QA-PFS, Q-TWiST considering grade ≥3 TEAEs, and Q-TWiST considering select grade ≥2 TEAEs were significantly longer with rucaparib than placebo in patients with a BRCA mutation and in the ITT population (table ). Across all age subgroups, QA-PFS and Q-TWiST (both analyses) were significantly longer with rucaparib than placebo (table 1 ). Conclusion: In the ITT population, BRCA -mutant subgroup, and age subgroups analysed, the quality-adjusted analyses, which incorporated patient-centred perspectives, confirmed the benefit of rucaparib vs placebo. Disclosure: NC: Clovis, Advaxis, AstraZeneca, BIOCAD, MSD, Pfizer, PharmaMar, Roche, Takeda, Tesaro AMO: Clovis, Amgen, Immunovaccine, Verastem, AstraZeneca, WebRx DL: Clovis, AstraZeneca, ImmunoGen, Merck, PharmaMar, Roche, Takeda, Tesaro CA: Clovis, Mateon, Bayer, Cerulean, Tesaro, VentiRx AO: Clovis, AstraZeneca, ImmunoGen, Genmab/Seattle Genetics, PharmaMar, Roche, Tesaro AD: Precision Oncology Australia, Shire, Specialised Therapeutics Australia JIW: AbbVie, AstraZeneca ARC: AstraZeneca, Roche, Clovis GS: Clovis, AstraZeneca, PharmaMar, Roche, Tesaro AL: Clovis, Pfizer, PharmaMar, GamaMabs, Merus, AstraZeneca RWH: Clovis, AstraZeneca, Tesaro MAG: Clovis, AstraZeneca, PharmaMar, Roche PCF: Clovis, AstraZeneca JCG: AstraZeneca, BMS, Janssen, Ipsen, MSD, Astellas DMO'M: Clovis, AstraZeneca, Gynecologic Oncology Group, Janssen, Myriad, Tesaro, Amgen, ImmunoGen, AbbVie, Ambry, Health Analytics, Agenus, Ajinomoto, Array, BMS, ERGOMED Clinical Research, Exelixis, Genentech, GSK, INC Research, inVentiv Health Clinical, Ludwig Institute for Cancer Research, Novartis, PRA International, Regeneron, Serono, Stemcentrx, TRACON DKA: Morphotek, Clovis, Advaxis, AstraZeneca, Pfizer, Syndax, Tesaro SB: Clovis, AstraZeneca, ImmunoGen, GamaMabs, Merck Serono, PharmaMar, Roche, Seattle Genetics, Tesaro JG-D: AstraZeneca, Clovis, Genentech/Roche, Janssen EMS: nothing to disclose JM: Modus Outcomes TC, LM, SG, JB: Clovis RLC: Clovis, AbbVie, AstraZeneca, Esperance, Janssen, Merck, Millennium, OncoMed, Roche/Genentech, Bayer, GamaMabs, Genmab, Gradalis, Millennium, Pfizer, Tesaro JAL: Clovis, AstraZeneca, Pfizer, Artios Pharma, Cristal Therapeutics, Merck/MSD, Regeneron, Roche, Seattle Genetics, Tesaro.